A family history of Hermansky–Pudlak syndrome complicated with pulmonary fibrosis: a case series and review. Issue 4 (9th March 2021) - Liendo Martinez, Katiuska; Pedraza, Fernando; Fuentes Alonso, Marta; Puente Maestu, Luis; Rodriguez Naranjo, Carla; De Miguel‐Diez, Javier
Abstract: The Hermansky–Pudlak syndrome (HPS) is a rare genetic disorder. We report three cases from a family of 12 siblings, with six albinos, of whom four and the father had pulmonary fibrosis (PF). Case 1 was admitted to our hospital due to increasing dyspnoea and history of gynaecological bleeding. Pulmonary function test showed a restrictive airflow pattern, high‐resolution computed tomographic scan demonstrated interstitial lung disease (ILD), and platelet aggregation was compromised with a reduced number of platelet dense bodies. The family history revealed endogamy and 11 members with suspected HPS. One of the albino sisters and the father had passed away with unidentified ILD, an albino brother died 14 years earlier, his autopsy had shown collections of ceroid pigments in the lungs, consistent with HPS, and another brother was followed up at our hospital for ILD and compromised platelet aggregation. This family probably has the highest number of members affected by HPS in Spain. Abstract : The Hernansky–Pudlak syndrome (HPS) is a rare genetic disorder with autosomal recessive inheritance characterized by oculocutaneous albinism and bleeding diathesis, and rarely lung involvement. We report three cases diagnosed with HPS from the same family of 12 siblings, with six albinos, of whom four and the father had pulmonary fibrosis. We believe these are interesting cases to report, especially for the lack of cases registered in Spain.